The role of Zip1 and Zip3 in cadmium accumulation in Fujian oyster (Crassostrea angulata) - Li, Huanhuan; Liang, Zhixiu; Wu, Longping; Ke, Yizhou; Que, Huayong; Shi, Bo (Frontiers in Marine Science, 2024)
Oysters are notably susceptible to accumulating substantial amounts of cadmium (Cd), leading to food safety concerns, yet the molecular mechanisms are not fully understood. Previous study identified a significant correlation between polymorphisms in the Zip1 and Zip3 of Fujian oyster (Crassostrea angulata) and the levels of Cd accumulation. Zip1 and Zip3, belonging to the Zip family, are primarily responsible for the cellular transport of zinc and other metal ions. To delve deeper into their roles in Cd transport within oysters, this research cloned and analyzed the sequences of Fujian oyster Zip1 and Zip3. The open reading frames for Zip1 and Zip3 were 960 and 978 bp, respectively, encoding proteins of 319 and 325 amino acids. Following Cd exposure, the expression levels of these genes in the mantle, gills, and other tissues initially increased significantly before decreasing, demonstrating a dose-dependent response. The lowest expression levels were observed in the adductor muscle, with Zip1 reaching its highest expression in the mantle and Zip3 in the visceral mass. In vitro RNAi experiments revealed that silencing Zip1 led to a 1.26-fold decrease in new 113Cd accumulation in the mantle, whereas silencing Zip3 resulted in a 1.29-fold increase. Immunohistochemistry showed weak expression of Zip1 and Zip3 proteins in the connective tissue of the mantle. In summary, Zip1 and Zip3 in Fujian oyster can transport Cd as a substrate, and played different roles in the absorption and efflux of Cd.